Chronic cluster headache: a French clinical descriptive study. Issue 12 (18th April 2007) - Donnet, A; Lanteri-Minet, M; Guegan-Massardier, E; Mick, G; Fabre, N; Géraud, G; Lucas, C; Navez, M; Valade, D; ,
Abstract : Background: Cluster headache (CH) is a relatively rare disease and episodic CH is more frequent than chronic CH. Few studies have described the characteristics of patients with chronic CH. Methods: This was a descriptive study carried out by eight tertiary care specialist headache centres in France participating in the Observatory of Migraine and Headaches (OMH). From 2002 to 2005, OMH collected data from 2074 patients with CH, of whom 316 had chronic CH. From January to June 2005, 113 patients with chronic CH were interviewed using standardised questionnaires during a consultation. Results: The male to female ratio was 4.65:1. Median age was 42 years. The majority of patients were smokers or former smokers (87%). 46% had primary chronic CH (chronic at onset) and 54% secondary chronic CH (evolving from episodic CH). Most patients had unilateral pain during attacks and 7% had sometimes bilateral pain during an attack. 48% reported a persisting painful state between attacks. Symptoms anteceding pain onset (mainly discomfort/diffuse pain, exhaustion, mood disorders) and auras were reported by 55% and 20% of patients, respectively. The functional impact of chronic CH was estimated as severe by 74% of patients, and 75.7% suffered from anxiety, as assessed by the Hospital Anxiety and Depression scale. There was no substantial difference in clinical presentation between primary and secondary CH. Discussion: This study confirms the existence of auras and interictal signs and symptoms in patients with chronic CH, and male sex and smoking as CH risk factors. Primary and secondary chronic CH appear equally prevalent. Male sex does not appear to favour the shift from episodic to chronic CH.